2022
DOI: 10.17521/cjpe.2021.0491
|View full text |Cite
|
Sign up to set email alerts
|

Variation of functional traits of alternative distribution of<i> Caragana</i> species along environmental gradients in Nei Mongol, China

Abstract: 摘 要 锦鸡儿属(Caragana)植物是蒙古高原干旱生态系统的重要组成成分, 沿着环境梯度形成了极为明显的地理替代分 布。为了检验这些替代分布种对气候和土壤环境变化的适应性, 该研究在内蒙古地区选择了41个样地、9种锦鸡儿属植物, 测 定了这些植物的株高(h)、叶性状(叶干物质含量(LDMC)、比叶面积(SLA)、叶面积(LA)、叶片氮含量(LNC)、叶片磷含量(LPC) 和氮磷比(N:P))和茎性状(茎组织密度(STD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Numerous studies have indicated that seasonal and interan-nual climate fluctuations are dominant factors driving plant phenotypic variation [58,63], especially variations driven by temperature and precipitation changes [58]. The 12 Caragana species investigated in this study are widely distributed across Inner Mongolia, Tibet, and Xinjiang, with significant differences in elevation and hydrothermal conditions among the sampling sites, contributing to the diversity of functional traits in this plant genus [18].…”
Section: Potential Roles Of Polymorphic Genic-ssrs In the Formation O...mentioning
confidence: 93%
See 2 more Smart Citations
“…Numerous studies have indicated that seasonal and interan-nual climate fluctuations are dominant factors driving plant phenotypic variation [58,63], especially variations driven by temperature and precipitation changes [58]. The 12 Caragana species investigated in this study are widely distributed across Inner Mongolia, Tibet, and Xinjiang, with significant differences in elevation and hydrothermal conditions among the sampling sites, contributing to the diversity of functional traits in this plant genus [18].…”
Section: Potential Roles Of Polymorphic Genic-ssrs In the Formation O...mentioning
confidence: 93%
“…Functional traits encompassed various parameters, including height (H), canopy coverage (CC), leaf thickness (LT), leaf dry mass (LDM), leaf wet mass (LWM), leaf dry mass content (LDMC), specific leaf area (SLA), stem volume (SV), stem diameter (SD), stem dry weight (SDW), stem tissue density (STD), total leaf area (TLA), leaf area (LA), stable carbon isotope 13C (δ13C), carbon biomass (Cmass), and nitrogen biomass (Nmass). These functional trait data were sourced from measurements conducted by Luo et al [18]. Climate factor data, such as longitude, attitude, altitude, annual mean temperature (BIO1), mean diurnal range (BIO2), isothermality (BIO3), temperature seasonality (BIO4), max temperature of the warmest month (BIO5), min temperature of the coldest month (BIO6), temperature annual range (BIO7), mean temperature of the wettest quarter (BIO8), mean temperature of the driest quarter (BIO9), mean temperature of the warmest quarter (BIO10), mean temperature of the coldest quarter (BIO11), annual precipitation (BIO12), precipitation of the wettest month (BIO13), precipitation of the driest month (BIO14), precipitation seasonality (BIO15), precipitation of the wettest quarter (BIO16), precipitation of the driest quarter (BIO17), precipitation of the warmest quarter (BIO18), and precipitation of the coldest quarter (BIO19), were obtained from the WorldClim database (https://www.worldclim.org/, accessed on 27 October 2022).…”
Section: Weighted Gene Co-expression Network Analysis and Hub Gene Id...mentioning
confidence: 99%
See 1 more Smart Citation